Pengaruh Kualitas Jasa Syariah, Kualitas Produk, Nilai Nasabah dan Kepuasan Nasabah terhadap Loyalitas Nasabah di Bank Muamalat Indonesia Cabang Kudus - Mohammad Sof’an; Fathimah Asri Mutmainnah (Fakultas Ekonomi dan Bisnis Universitas Islam Nahdlatul Ulama Jepara, 2022)
The Influence of Sharia Service Quality, Product Quality, Customer Value and Customer Satisfaction on Customer Loyalty at Bank Muamalat Kudus. The purposes of this study are: first, to test empirically the effect of the quality of sharia services at Bank Muamalat Kudus on customer loyalty. Second, to empirically test the effect of Bank Muamalat Kudus product quality on customer loyalty. Third, to empirically test the effect of Bank Muamalat Kudus customer value on customer loyalty. Fourth, to empirically test the effect of Bank Muamalat Kudus customer satisfaction on customer loyalty. This study uses a field research approach with a questionnaire method that is distributed directly to the customers of Bank Muamalat Kudus as many as 100 respondents. The sampling technique used was accidental sampling. The data analysis technique used multiple linear regression analysis. The findings of this study are: first, the quality of Islamic services has an influence on customer loyalty of Bank Muamalat Kudus as evidenced by the results of the value of tcount > ttable. This can be seen from the tcount value of 3.034 > ttable of 1.984 with a significance level below 5%. Second, product quality has an influence on customer loyalty of Bank Muamalat Kudus as evidenced by the value of tcount > ttable. This can be seen from the tcount value of 3.166 > ttable of 1.984 with a significance level below 5%. Third, customer value has an influence on customer loyalty to Bank Muamalat Kudus customers, as evidenced by the results of the value of tcount > ttable. This can be seen from the tcount value of 2,976 > ttable of 1,984 with a significance level below 5%. Fourth, customer satisfaction has an influence on customer loyalty of Bank Muamalat Kudus as evidenced by the results of the value of tcount > ttable. It can be seen that the tcount value is 2.799 > ttable is 1.984 with a significance level below 5%